2021
DOI: 10.3389/fimmu.2021.763433
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Lymphopenia Analysis in Younger and Older Patients With Multiple Sclerosis Treated With Cladribine Tablets

Abstract: Cladribine tablets (CladT) preferentially reduce B and T lymphocyte levels. As aging is associated with a decline in immune function, the effect of CladT on lymphocyte levels may differ by age. This post hoc analysis combined data from the Phase 3 CLARITY, CLARITY Extension, and ORACLE-MS studies to examine the effect of age (≤50 or >50 years) on lymphopenia following CladT 3.5 mg/kg (CladT3.5; cumulative dose over 2 years) treatment over 96 weeks. Both CladT3.5 and placebo were given over Weeks 1 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Post hoc integrated analyses of data from the CLARITY and ORACLE-MS studies showed that the aggregate incidence of lymphopenia as an SAE was 0.1 event/100 patient-years for CladT [ 24 ] and 0/100 patient-years for placebo (Fig. 2 ) and that the time course of effects of CladT on immune cells was similar for patients above or below age 50 years [ 42 ].…”
Section: Adverse Events Of Special Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Post hoc integrated analyses of data from the CLARITY and ORACLE-MS studies showed that the aggregate incidence of lymphopenia as an SAE was 0.1 event/100 patient-years for CladT [ 24 ] and 0/100 patient-years for placebo (Fig. 2 ) and that the time course of effects of CladT on immune cells was similar for patients above or below age 50 years [ 42 ].…”
Section: Adverse Events Of Special Interestmentioning
confidence: 99%
“…These data confirmed the results of earlier integrated analyses [ 91 , 92 ]. There has been no suggestion of clustering of specific cancer types or haematological cancers in CladT-treated populations to date [ 24 , 42 ].
Fig.
…”
Section: Adverse Events Of Special Interestmentioning
confidence: 99%
“…Cladribine treatment is one of the most recently approved MS medicine. The mechanism of action of cladribine results in profound, rapid and long-lasting reductions of CD4 + and CD8 + T cells, as well as B cells, each in their magnitude and kinetics [17] , [34] , [35] . Cladribine is widely recognized as a T and B cell inhibitor, particularly emphasizing its T cell inhibitory effects as the primary mechanism of action.…”
Section: Methodsmentioning
confidence: 99%
“… Reproduced from ref. [ 64 ] according to the terms of the Creative Commons Attribution License (CC BY) ( http://creativecommons.org/licenses/by/4.0/ ) …”
Section: Changes In the Efficacy Of Disease-modifying Therapy With Agementioning
confidence: 99%
“…A real-world analysis comprising data from spontaneous adverse event reporting and post-marketing studies estimated the incidence of severe lymphopenia as 0.12 events/100,000 person-years of treatment [ 63 ]. A pooled analysis estimated the incidence of lymphopenia in those who received CladT according to age [ 64 ] using data from the CLARITY study [ 55 ] and its extension [ 65 ] and the ORACLE study in clinically isolated syndrome (total N = 1564) [ 66 ]. The incidence of grade 3 lymphopenia during year 1 of treatment with CladT was 8.3% (age < 50 years) and 10.0% (age ≥ 50 years) and no grade 4 lymphopenia occurred at this time.…”
Section: Changes In the Efficacy Of Disease-modifying Therapy With Agementioning
confidence: 99%